Analisis Pengelolaan Ziswaf Untuk Meningkatkan Kesejahteran Masyarakat Dibidang Ekonomi : Studi Kasus Ybm Pln Uid Wilayah Sumatera Utara - Suci Rahmida; M. Ridwan (Transformasi: Journal of Economics and Business Management, 2023)
Poverty is a condition that is still a problem in Indonesia. This can be seen from the still high number of poor people in Indonesia in 2021 reaching 26.5 million people. This poverty does not just happen, one of the reasons is because people's income is low and the poverty level is still low, making them unable to meet their daily needs. Eradicating poverty in Indonesia requires cooperation from various parties, both government and private. Therefore, the community service team together with YBM PLN UID North Sumatra is implementing a program based on local wisdom to improve the community's economy in the form of community empowerment in improving community welfare. This has an impact on people's income levels which are still low. This program includes providing business capital, skills training and business assistance. The results of the analysis of Ziswaf management for economic prosperity show that this program has a positive impact on community welfare. This can be seen from the aspect of increasing income, physical aspects, natural aspects, human resource aspects, and social aspects.